What does the public know about technological solutions for achieving carbon neutrality? Citizens' knowledge of energy transition and the role of media - Arlt, Dorothee; Schumann, Christina; Wolling, Jens (Frontiers in Communication, 2023)
The present study explores the relation between media use and knowledge in the context of the energy transition. To identify relevant knowledge categories, we relied on the expertise of an interdisciplinary research team. Based on this expertise, we identified awareness-knowledge of changes in the energy system and principles-knowledge of hydrogen as important knowledge categories. Based on data obtained from a nationwide online survey of the German-speaking population (n = 2,025) conducted in August 2021, we examined the level of knowledge concerning both categories in the German population. Furthermore, we studied its associations with exposure to journalistic media and direct communication from non-media actors (e.g., scientists). Our results revealed a considerable lack of knowledge for both categories. Considering the media variables, we found only weak, and in some cases even negative, relations with the use of journalistic media or other actors that spread information online. However, we found strong associations between both knowledge categories and the control variables of sex, education, and personal interest. We use these results to open up a general discussion of the role of the media in knowledge acquisition processes.